Healing potentials of mixture of Zingiber officinale, Curcuma domestica and Garcinia kola extracts on Renal and Hepatic tissues of Rats pre-treated with Cyclophosphamide - I. Iyare , Godfrey; T. Omorodion, Nosa (Nigerian Journal of Pharmaceutical and Applied Science Research, 2023)
Background: Zingiber officinale, Curcuma domestica, and Garcinia kola have been a regular feature in herbal medicine as typical feedstocks. They are mainly used as antibiotics and anti-inflammatory agents. This research work was designed to further investigate ethnobotanical uses of these plants to ascertain their ameliorative roles the on cyclophosphamide effect on histopathological and biochemical indices of renal and hepatic tissues of albino rats. Methods: The study used 40 rats in all and was done in two phases. Two groups were created for phase 1, group 1 (n = 6) fed with rat feed and water served as the control group; group 2, (34 rats) was given 10 mg/kg of cyclophosphamide. The animals were weighed, anesthetized, and 6 of the 34 rats (in group 2) were randomly selected and sacrificed after 5 weeks; blood samples, livers and kidneys were examined histologically. In phase 2, the remaining 28 rats were divided into seven groups (A, B, C, D, E, F, and G, n = 4) and treated with different doses of individual and combined extracts of the plants. After six weeks, the blood samples, livers and kidneys of all the animals were histologically analyzed. Results: There were significant (P< 0.05) increases in aspartate aminotransferase, alkaline phosphatase, and alanine transaminase as well as degenerative effects on the liver and kidney, which were significantly decreased by treatment with different combinations of the extracts. Conclusion: The plants extract could serve as remedial treatment renal and hepatic problems as well as healthy food for mankind.